Differences in Glyphosate-Resistant Weed Management Practices over Time and Regions. (March 2016) - Zhou, Xia "Vivian"; Roberts, Roland K.; Larson, James A.; Lambert, Dayton M.; English, Burton C.; Mishra, Ashok K.; Falconer, Lawrence L.; Hogan, Robert J.; Johnson, Jason L.; Reeves, Jeanne M.
Abstract : The objective of this research was to describe proportional differences across time and region in management practices among southern cotton farmers who experienced glyphosate-resistant (GR) weeds on their farms earlier than those who experienced them later and among farmers who were closest to one of four historical outbreak epicenters: Lauderdale County, TN; Macon County, GA; Edgecombe County, NC; and Terry County, TX. A mail survey was conducted with cotton farmers in 2012 from 13 southern, cotton-producing states. Survey responses on practices used by farmers were classified into three broad categories of labor, mechanical/tillage/chemical (MTC), and cultural. Proportions of respondents using practices from each category were identified by time and region; across which, proportional-difference tests were conducted. Results indicated respondents encountering GR weeds earlier were more likely than farmers who experienced them later to use the three broad-category practices (labor, 98 vs. 92%; MTC, 95 vs. 89%; and cultural, 86 vs. 76%) and specific practices, including hooded sprayers (76 vs. 58%), in-season herbicide change (83 vs. 60%), and field-border management (60 vs. 35%). Also, respondents closest to Lauderdale County were more likely than farmers closest to Edgecombe County to use broad-labor practices (99 vs. 91%) and specific practices, including hand hoeing (96 vs. 84%), hand spraying (49 vs. 31%), spot spraying (76 vs. 59%), wick applicator (13 vs. 11%), and field-border management (58 vs. 39%). Education programs on weed management can be developed and tailored according to the time and regional differences to provide effective information and communication channels to farmers.